Indirect biofed architecture: Strategies to best utilise biofeedback tools and interaction metaphors within digital architectural environments - Champion, Erik; Dekker, A. (CAADRIA, 2015)
This paper explains potential benefits of indirect biofeedback used within interactive virtual environments, and reflects on an earlier study that allowed for the dynamic modification of a virtual environment’s graphic shaders, music and artificial intelligence (of Non Playing Characters) based on the biofeedback of the player. It then examines both the potential and the issues in applying biofeedback(already effective for games) to digital architectural environments, and suggests potential uses such as personalization, object creation, atmospheric augmentation, filtering, and tracking.